COLLABORATIVE GOVERNANCE STRATEGY IN SLUM ARRANGEMENT THROUGH COMMUNITY ACTION PLAN (CAP) AND (COLLABORATIVE IMPLEMENTATION PROGRAM) CIP IN THE TAMBORA AREA, DKI JAKARTA PROVINCE - Irawati, Riya; Rivai, Firman Hadi; Rahayu, Neneng Sri (DIA: Jurnal Administrasi Publik, 2025)
The Central Statistics Agency (BPS) 2021 stated that only 48.48% of households had their own houses in Jakarta throughout 2021 while the rest were still in irregular status. The selection of the study area is supported by several problem issues, including Tambora has a high density of 49,841 people/km2, into extreme poor areas and there are still physical problems in the residential, social and economic environment. The DKI Jakarta Provincial Government in overcoming the problem of settlement arrangement has issued a program Community Action Plan (CAP) and Collaborative Implementation Program (CIP). The analysis of the research was carried out by analyzing factors based on the approach of Ansell and Gash (2008), Edward DeSeve and H. Moore (2009) and Nabatchi and Leighninger (2015) and then formulated the best strategy using IFE and EFE analysis, SWOT and QSPM. The conclusion drawn is that it is not optimal Collaborative Governance caused by several factors that have not performed well, namely public participation factors, governance Governance, commitment to goals and access to resources while good factors are transparency and accountability. Optimization strategy Collaborative Governance which were formulated include 1) Partnership, 2) Policy Integration, 3) Political Commitment, 4) Human Resources Improvement and 5) Upgrade Program.